(√2 + √5 - √7)^2·(√2 + √5 - √7)^2
= ((√2 + √5 - √7)·(√2 + √5 - √7))^2
= (2 + √10 - √14 + √10 + 5 - √35 - √14 - √35 + 7)^2
= (14 + 2·√10 - 2·√14 - 2·√35)^2
= (14 + 2·√10 - 2·√14 - 2·√35)·(14 + 2·√10 - 2·√14 - 2·√35)
= (196 + 28·√10 - 28·√14 - 28·√35) + (28·√10 + 40 - 4·√140 - 4·√350) + (- 28·√14- 4·√140+ 56 + 4·√490) + (- 28·√35 - 4·√350 + 4·√490 + 140)
= 196 + 40 + 56 + 140 + 56·√10 - 56·√14 - 56·√35 - 8·√140 - 8·√350 + 8·√490
= 432 + 56·√10 - 56·√14 - 56·√35 - 16·√35 - 40·√14 + 56·√10
= 432 - 72·√35 - 96·√14 + 112·√10
Keine Ahnung wie du da auf die Lösung 40 kommen sollst. Schau mal ob du die Aufgabe richtig abgeschrieben hast.